Theater and crisis: myth, memory, and racial reckoning in America, 1964-2020 - Rankine, Patrice D. (Lever Press, 2024)
Racial reckoning was a recurrent theme throughout the summer of 2020, a response to George Floyd’s murder and the unprecedented impact of COVID on marginalized groups. Theater and Crisis proposes a literary and theatrical study of how Floyd's killing could possibly happen in the aftermath of the Civil Rights era, and in the supposedly post-racial era following the election of Barack Obama. In the days and months following Floyd's death, there were nightly protests in streets across the United States and broader world. At the same time, theater performances were forced to shift online to video conferencing platforms and to find new ways to engage audiences. In each case, groups made shared meaning through storytelling and narrative, a liberatory process of myth-making and reverence that author Patrice D. Rankine calls “epiphanic encoding.” Rather than approaching the problem of racial reckoning through history, where periodization and progress are dominant narratives, Theater and Crisis argues that myth and memory allow for better theorization about recurring events from the past, their haunting, and what these apparent ghosts ask of us. Building on the study of myth as active, processual storytelling, Rankine acknowledges that it grounds and orients groups toward significant events. Theater and Crisis aligns narratives about Emmett Till, Trayvon Martin, and George Floyd, among others, with ancient, mythic figures such as Christ, Dionysus, Oedipus, and Moses. As living and verbal visitations, these stories performed on stage encode the past through their epiphanies in the present, urging audiences toward shared meaning. Rankine traces the cyclical hauntings of race through the refiguring of mythic stories across the past 75 years in the plays of James Baldwin, Ntozake Shange, Antoinette Nwandu, and many more, and in response to flashpoints in US racial history, such as the 1955 lynching of Emmett Till, the upheavals of the 1960s and 1970s, the wars on drugs and crime, and the continued violence against and disenfranchisement of Black people into the twenty-first century. Theater and Crisis explores the appearance of myth on the American stage and showcases the ongoing response by the theatrical establishment to transform the stage into a space for racial reckoning. This timely book is essential reading for scholars of theater studies, classics, and American studies.